Idiopathic peripheral enthesopathy without spondylarthritis. Issue 9 (September 1986) - Nishikai, M; Sugimoto, M; Sato, A; Takeuchi, H
Abstract : A 40 year old man who had a systemic inflammatory enthesopathy without spondylarthritis and HLA-B27 is described. The presence of hypergammaglobulinaemia and the effectiveness of glucocorticoid therapy suggested the possibility of its aetiology being 'autoimmune' in nature.